God’s Law in.Russian school at the first half of the XIXth century - Kalinina Elena (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In the represented work the problems of the system of teaching the Law of God in the Russian Empire at the end of the XVIIIth - ﬁrst half of the XIXth century are examined. This subject was compulsory in all educational programs of secondary schools. However, despite considerable government support, certain problems of religious education were revealed in schools. In this article the issues of teaching the Law of God in Russian schools at the end of the XVIIIth - ﬁrst half of the XIXth century are considered on the basis of documentary materials from the four archives: Central state historical archive of St. Petersburg, the Russian state historical archives, the national archives of the Republic of Karelia, State archive of Archangelsk region. Memoirs of pupils published in the Central and regional periodicals and in the memoirs of the second half of the XIXth - beginning of the XXth century were used in the studying. In Russian historiography the issue of religious education in the pre-reform school remains little- known chapter of national education history. Researchers were more interested in the activities of the Spiritual Department and the Ministry of national education on organization and formation of the network of educational institutions. Currently, issue of teaching “Bases of Orthodox culture” in Russian schools becomes a special subject. In this connection attention to the origin of putting a compulsory subject of the law of God into the school program, and the participation of the clergy in educational work in educational institutions in the ﬁrst half of the XIXth century is vital today. The present work provides a new look at studying of the problem and gives new directions for research.